2016
DOI: 10.1177/1557988316679563
|View full text |Cite
|
Sign up to set email alerts
|

“You Can’t Just Walk Down the Street and Meet Someone”: The Intersection of Social–Sexual Networking Technology, Stigma, and Health Among Gay and Bisexual Men in the Small City

Abstract: Social–sexual networking technologies have been reported to yield both psychosocial benefits and sexual risks for gay and bisexual men, yet little research has explored how technology interacts with the social–geographical environment to shape the health of gay and bisexual men in the relatively understudied environment of small cities. This article draws on 29 semistructured interviews examining the use of social–sexual networking technologies among racially diverse gay and bisexual men in two small cities. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 49 publications
(78 reference statements)
2
24
0
Order By: Relevance
“…The Internet also offers access to virtual spaces that LGBTQ people, particularly LGBTQ youth, perceive to be safer to socialize in than offline settings (Gay, Lesbian, & Straight Education Network, 2013; Hillier et al, 2012; White Hughto, Pachankis, Eldahan, & Keene, 2016). Capitalizing on the familiarity of online settings, researchers have begun to explore the health of LGBTQ populations through online focus group discussions (DuBois et al, 2015; Thomas et al, 2013; Woodyatt et al, 2016; Ybarra et al, 2014).…”
Section: Online Focus Groups: History Methodological Considerationsmentioning
confidence: 99%
“…The Internet also offers access to virtual spaces that LGBTQ people, particularly LGBTQ youth, perceive to be safer to socialize in than offline settings (Gay, Lesbian, & Straight Education Network, 2013; Hillier et al, 2012; White Hughto, Pachankis, Eldahan, & Keene, 2016). Capitalizing on the familiarity of online settings, researchers have begun to explore the health of LGBTQ populations through online focus group discussions (DuBois et al, 2015; Thomas et al, 2013; Woodyatt et al, 2016; Ybarra et al, 2014).…”
Section: Online Focus Groups: History Methodological Considerationsmentioning
confidence: 99%
“…For example, National HIV Behavioral Surveillance (NHBS) data among MSM in San Francisco observed that men recruited in venues that serve alcohol report greater frequency of binge drinking, number of drinking days, and number of drinks in a typical drinking day [ 8 ]. Another concern with venue-based recruitment is the decline in attendance at “physical gay spaces”, such as clubs and bars, as increasing number of MSM turn to “virtual gay communities” (e.g., social-networking spaces within internet and mobile applications)[ 19 21 ]. Additionally, recruiting diverse MSM samples in studies has proved challenging for researchers, who have reported difficulties in enrolling youth and men of color, limiting external validity [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smaller cities often differ from larger cities in terms of stigma [29,30] and availability of visible gay spaces [31][32][33]. As others have noted, research on sexual health and appfacilitated sexual behavior among MSM in mid-sized cities is limited [34][35][36].…”
Section: Resultsmentioning
confidence: 99%